Factors Influencing Choice of Pesticides Used by Grain Farmers in Southwest Nigeria (2014)
Pesticide use in agriculture has caused a lot of rising concerns about the safety of residues in food and water, as well as other potential health and environmental risks. There is need therefore to determine the factors that influence farmers’ choice of pesticides for post-harvest grain storage. This study therefore examines the factors influencing the choice of pesticides used by grain farmers in South-Western, Nigeria. Data for this study were collected using multi-stage sampling techniques and a total number of 192 respondents were sampled. The tools used for analysis include descriptive statistics (used to profile the socio-economic characteristics of the respondents) and probit model (used to determine the factors influencing the choice of pesticides by the grain farmers). Results from this research indicates that majority (69.79%) of the grain farmers had formal education, with above 10 years of farming experience (96.88%) and within the age bracket of 30 years and above (95.83%). The probit results also shows that the age of household head, education, farming experience, price of grains and quantity of grains consumed were significant factors that influences the choice of pesticides used by the grain farmers in the study area. It was recommended that farmers should be educated on the use of pesticides to avoid hazards